Value-based healthcare translated: a complementary view of implementation - Christian Colldén; Andreas Hellström (BMC, 2018)
Abstract Background Interest in the implementation of various innovations (e.g. medical interventions and organizational approaches) has increased rapidly, and management innovations (MIs) are considered particularly complex to implement. In contrast to a traditional view that innovations are implemented, some scholars have promoted the view that innovations are translated into contexts, a view referred to as translation theory. The aim of this paper is to investigate how a translation theory perspective can inform the Consolidated Framework of Implementation Research (CFIR) to increase understanding of the complex process of putting MIs into practice. The empirical base is a two-year implementation of the MI Value-Based Health Care (VBHC) to a psychiatric department in a large Swedish hospital. Methods In this longitudinal case study, a qualitative approach was applied using an insider researcher with unique access to data, who followed the implementation starting in 2015. Data sources includes field notes, documents, and audio recordings of meetings and group reflections which were abridged into an event data file structured by CFIR domains. In a joint analysis, an outsider researcher was added to strengthen the analysis and mitigate potential bias. Results Two themes were identified, for which CFIR did not satisfactorily explain the findings. First, the intervention characteristics (i.e. the content of the MI) were modified along the process and, second, the process did not follow predefined plans. However, the project was still perceived to be successful by internal and external stakeholders. Conclusions The paper proposes three ways in which translation theory can inform CFIR when applied to MIs: 1) strength of evidence is not as important for MIs as for medical and technical innovations; 2) adaptability of the MI can be emphasized more strongly, and 3) it can be more fruitful to view implementation as a dynamic process rather than seeing it as a matter of planning and execution. For managers, this implies encouragement to seize the opportunity to translate MIs to fit their organization, rather than to aim to be true to an original concept.